Profil Tingkat Kebugaran Jasmani Pada Peserta Didik SMP Negeri 1 Eris Tondano - Patrik Sarapung (STIKES Columbia Asia Medan, 2025)
This study aims to determine the physical fitness profile of students at SMP Negeri 1 Eris Tondano. This research employed a descriptive method with a survey technique involving 62 students, consisting of 38 males and 24 females. The data collection instrument used was a 12-minute run test based on the Cooper protocol. The results showed that the average level of physical fitness was classified as “bad” with an overall mean distance of 1606.47 meters. Male students had an average of 1900.84 meters, while female students averaged 1140.38 meters. According to Cooper’s classification, 73% of the students fell into the “bad” category and 27% were in the “reasonable” category. The conclusion of this study is that the physical fitness level of students remains low and requires more structured attention and guidance through physical education programs.